To the issues of implementation of the state employment program in the regional labor market - Konurbayeva, Zh.T.; Madiyarova, E.S.; Myrzabayeva, S.; Karayilmazlar, E. (BUKETOV BUSINESS REVIEW, 2018)
The article presents the results of a study on the impact of the state program «Dorozhnaya karta zanyatosti2020» on the labor market indicators of the East Kazakhstan region. The problems of the labor market should be known by both economists and politicians otherwise unresolved problems can lead to irrational use of the main productive forces of society - labor resources, loss of competitive advantages of the country due to the decrease in the human resources potential, but also turn into serious social conflicts. Therefore it is necessary to deal with the problems of employment, improving methods and forms of state intervention in the labor market functioning with effective institutional changes, especially in the period of the growth of economic crises. The DKZ-2020 program was developed for preservation of the level of employment in the period of temporary economic difficulties. Program included mechanisms for anti-crisis response, increase of efficiency labor market regulation, involving the population in active measures to promote employment. All directions of DKZ-2020 are considered separately, positive aspects and minuses of the program components are indicated, as well as their impact on the main indicators of the labor market in the region.The analysis showed that the goals of the DKZ-2020 program were achieved,that state programs on the promotion of employment significantly increase the level of employment of the population and a labor market regulation is a priority in public policy.